2002
DOI: 10.1046/j.1439-0442.2002.00343.x
|View full text |Cite
|
Sign up to set email alerts
|

Reverse 3,3′,5′‐Triiodothyronine Suppresses Increase in Free Fatty Acids in Chickens Elicited by Dexamethasone or Adrenaline

Abstract: Reverse triiodothyronine (rT3) displays hypometabolic properties and antagonizes the hypermetabolic effect of 3,5,3'-triiodothyronine (T3). Previous experiments revealed that exogenous rT3 enhanced free fatty acids (FFA) in heat-stressed pullets and in chickens infected with lipopolysaccharide from Escherichia coli. To gain more data concerning the action of rT3, its effect on lipaemia produced by two main stress hormones: glucocorticoids and catecholamines, has been investigated. Synthetic glucocorticoid [dex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…rT3 may also modulate avian lipid metabolism response to epinephrine and steroids (23). The activity of DIO2 (D2) in murine neuroblastoma cells may also be reduced by rT3 (24).…”
Section: Bioactivity Of Rt3mentioning
confidence: 99%
“…rT3 may also modulate avian lipid metabolism response to epinephrine and steroids (23). The activity of DIO2 (D2) in murine neuroblastoma cells may also be reduced by rT3 (24).…”
Section: Bioactivity Of Rt3mentioning
confidence: 99%
“…Using high‐performance liquid chromatography method the technical service of Calbiochem‐Novabiochem was not able to detect impurities in the form of T 3 , T 4 and 3,3′‐T 2 in rT 3 preparation, lot no. 606523 (Bobek et al., 2002).…”
Section: Methodsmentioning
confidence: 99%
“…In the former experiment (Bobek et al., 2002) it has been shown that synthetic dexamethasone or adrenaline‐induced hyperlipaemia in blood plasma was significantly reduced after administration of rT 3 . The aim of this study was to learn if such an effect could be repeated in physiological conditions by endogenous corticosterone and catecholamines.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, in chicken, rT 3 repressed the increase in the levels of circulating FFA induced by dexamethasone and adrenaline (Bobek et al . ).…”
Section: Reverse Triiodothyroninementioning
confidence: 97%